(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Î²-glucosidases have characteristics of biotechnological interest and have thus become important industrial enzymes.In this study, Î²-glucosidase produced by Trichoderma viride from cow dung was subjected to a three step purification process involving ammonium sulphate precipitation, gel filtration by Sephadex G-100 and ion exchange chromatography by DEAE-Sephadex A-25. The elution profile on Sephadex G-100 resulted in a single broad peak (fractions 9-21) which had a yield of 3.7% and a purification fold of 4.29 with a specific activity of 25.70 Âµmol/min/mg proteins while the elution profile on DEAE-Sephadex A-25 resulted in a single broad peak (fraction 8-14) which had a yield of 2.76% and a purification fold of 22.14 with a specific activity of 132.41Âµmol/min/mg of protein. The purified enzyme was obtained as a single band and had a molecular mass of 51.8 kDa on SDS-PAGE. This results provide support for further studies of this enzyme towards revealing its potential biotechnological applications.